Predicting Dishonesty When the Stakes Are High: Physiologic Responses During Face-to-Face Interactions Identifies Who Reneges on Promises to Cooperate - Zak, Paul J.; Barraza, Jorge A.; Hu, Xinbo; Zahedzadeh, Giti; Murray, John (Frontiers in Behavioral Neuroscience, 2022)
Trust is risky. The mere perception of strategically deceptive behavior that disguises intent or conveys unreliable information can inhibit cooperation. As gregariously social creatures, human beings would have had to evolved physiologic mechanisms to identify likely defectors in cooperative tasks, though these mechanisms may not cross into conscious awareness. We examined trust and trustworthiness in an ecological valid manner by i) studying working-age adults, ii) who make decisions with meaningful stakes, and iii) permitting participants to discuss their intentions face-to-face prior to making private decisions. In order to identify why people fulfill or renege on their commitments, we measured neurophysiologic responses in blood and with electrodermal activity while participants interacted. Participants (mean age 32) made decisions in a trust game in which they could earn up to $530. Nearly all interactions produced promises to cooperate, although first decision-makers in the trust game reneged on 30.7% of their promises while second decision-makers reneged on 28%. Those who reneged on a promise had elevated physiologic stress using two measures (the change in adrenocorticotropin hormone and the change in skin conductance levels) during pre-decision communication compared to those who fulfilled their promises and increased negative affect after their decision. Neurophysiologic reactivity predicted who would cooperate or defect with 86% accuracy. While self-serving behavior is not rare, those who exhibit it are stressed and unhappy.